Nearly half of HIV-positive children attending public health facilities are suffering from chronic under-nutrition in conflict-affected zones of Southern Ethiopia - Abraham, Awoke; Kawuki, Joseph; Aragie, Tesfaye; Elias, Cherinet; Birahanu, Zewudu; Dawit, Desalegn; Israel, Eskinder (Frontiers in Nutrition, 2024)
In combination with HIV infection, malnutrition is a complicated medical condition with high morbidity and mortality rates in affected children due to a variety of socioeconomic and medical etiological variables. To combat this, information from a range of contexts is required, but there is little evidence, particularly about the nutritional status of under fifteen living with HIV in impoverished communities such as conflict affected areas. Therefore, in this study the magnitude and related factors of stunting among under fifteen children antiretroviral therapy at public health facilities was assessed Methods: An institution-based cross-sectional study was conducted among under fifteen children living with HIV in conflict-affected zones of Southern Ethiopia. After providing written informed consent to study participants, data were collected using an interviewer-administered questionnaire and anthropometric measurements. Bivariable and multivariable logistic regression models were used to identify factors associated with nutritional status, using SPSS Version 25.Results: Of the 401 participants, 197 (49.1%, 95%CI: 0.44, 0.54) had height-for-age z-score <=-2. In the multivariable analysis, larger household size (AOR=1.58, 95%CI: 1.04-2.40), dietary diversity (AOR=1.78; 95%CI: 1.07-2.96) and having a history of recurrent diarrhea (AOR=1.96; 95%CI:1.07-3.59) were significantly associated with chronic undernutrition.The prevalence found in this study was high when compared with the stunting target set in SDG, which states to end all forms of malnutrition. In order to mitigate the negative health effects of diarrhea during HIV therapy, extra attention needs to be paid to facilitate timely detection and on-going monitoring. Nutrition programs in conflict-affected areas need to consider households with larger family sizes and/or routinely having fewer food groups.